Distinguishing Corruption in Law and Practice: Empirically Separating Conviction Charges from Underlying Behaviors. (2nd January 2019) - Albanese, Jay S.; Artello, Kristine; Nguyen, Linh Thi
Abstract : This analysis examines the precise laws under which corruption cases are brought and trends over time in order to assess how the underlying corruption behaviors can be grouped into types. Corruption is operationalized into several distinct types of misconduct under law for purposes of prosecution. Federal defendants were most often charged with offenses charging bribery, fraudulent statements/entries, theft of public funds, conspiracy, and fraudulent claims (in that order). Whereas state and local defendants were more likely to be charged with a different ordering of offenses (extortion, theft from government programs, mail fraud, and conspiracy for state defendants, and theft from government programs, extortion, mail fraud, and bribery for local defendants). These differences in the corruption choices by public officials at different levels of government have rarely been considered. Preliminary explanations are offered for these differences, which provide insights into the way in which corruption occurs in different jurisdictions.